PEMBELAJARAN GEOGRAFI PADA JAM TERAKHIR: PERMASALAHAN DAN SUATU SOLUSI YANG DITAWARKAN - Asofi, Tuti Supriyanti (Jurnal Geografi, 2013)
This classroom action research aims to improve studentâs response to a givengeography lesson at last class lesson in XI IPS-at SMA Negeri 1 Karangreja theacademic year 2010/2011. The problems that the writer formulated to uncover theabove phenomenon is âwhat kind of an innovative teaching model which iscapable of increasing the studentâs responses to the lesson studied Geography inclass?. The results showed a positive effect on the use of models in the teachinglearningprocess in teaching Geography. Student responses increasedsignificantly during treatment in the study. Application of PARAMEK teachingmodel in teaching and learning geography subjects make students more active,working with a good spirit and enjoy the process in the classroom.